2007
DOI: 10.1590/s0100-39842007000600010
|View full text |Cite
|
Sign up to set email alerts
|

Radioproteção, dose e risco em exames radiográficos nos seios da face de crianças, em hospitais de Belo Horizonte, MG

Abstract: OBJETIVO: Avaliar a freqüência das incidências radiográficas realizadas nos seios da face de pacientes pediátricos em hospitais de Belo Horizonte, MG, as condições de radioproteção, as técnicas radiográficas empregadas, o kerma no ar de entrada e as doses nos órgãos mais expostos. MATERIAIS E MÉTODOS: Foram coletados os dados dos pacientes e parâmetros de técnica radiográfica empregados em exames de crianças de 1 a 16 anos de idade, em cinco salas de quatro hospitais da cidade, observando, também, aspectos de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It was observed that the protection was incipient and that two incidences were frequently requested unnecessarily. 12 …”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the protection was incipient and that two incidences were frequently requested unnecessarily. 12 …”
Section: Discussionmentioning
confidence: 99%
“…This latter method, employing radiographic technique parameters in association with measurements of the x-ray equipment output is usually appropriate for this purpose (6) . Based on K e , magnitudes related to risks, such as dose to organs, can be obtained with appropriate conversion coefficients shown in tables available in the literature (11,12) or by means of some softwares (13)(14)(15)(16) . So, based on the dose to organ, the risk of an exposed individual for developing a determined type of cancer (in the irradiated organ) as compared with a non-exposed individual can be determined with the aid of appropriate models available in the literature (17) .…”
Section: Introductionmentioning
confidence: 99%